Comparação entre a moldagem por injeção e a manufatura aditiva utilizando materiais poliméricos reciclados: um estudo de acv - Garcia, Fabricio Leon (2018)
With society increasing concern regarding the environmental impacts generated by production processes and products, it has been growing the necessity for studies that analyze new technological alternatives of the manufacturing towards cleaner production. With the recent technological advance, additive manufacturing (AM) deserves some attention, which has been gaining space in the industries due to the possibility of working with pieces of different geometric shapes, and distributing the production along the value chain. In this context, a comparative analysis was performed between two manufacturing processes, one conventional (CM), injection molding, and another additive (Fused Deposition Modelling (FDM)), to evaluate their potential environmental impacts, identifying the main environmental hotspots and analyzing the influence of the infill through the AM on the environmental performance of the process. The Life Cycle Assessment (LCA) methodology was adopted, which has an holistic profile, and it allows a powerful evaluation of the environmental performance of a process or product. In order to carry out the study, pieces of acrylonitrile butadiene styrene (ABS) recycled from waste of electrical and electronic equipment (WEEE) were produced on both processes. The results indicate a lower environmental impact of the AM when it is aimed to produce a batch size smaller than 14 pieces, and above 50 pieces the CM generated less impact, for the global warming potential (GWP) and Cumulative energy demand (CED). In order to better analyze the processes, the UPLCI (Unit Process Life Cycle Inventory) methodology was adopted, which resulted in an impact assessment layered by each mode of operation / process step of the equipment studied. For the AM, the printing stage was the one that contributed the most for generating impacts. In CM, the main factors responsible for generating impacts were the injection phase, followed by the consumption of raw material. Mechanical tensile tests were carried out with the pieces obtained by the AM with different infills (25%, 50%, 75% and 100%). It was possible to observe that, even with 100% filling, the printed parts presented a mechanical performance lower than those made from the CM. In addition, when the values obtained for the tensile strength and the generated impact (GWP) were analyzed for each infill of the pieces obtained by the AM, it was observed that the pieces with 100% of filling obtained the best relation between better mechanical properties and lower environmental impact.